The Relationship between Pakistani ESL Learners’ Beliefs and Their Learning Strategies - Sibtain, Masroor; Qasim, Hafiz Muhammad; Hassan, Waqar (International Journal of Psychosocial Rehabilitation, 2020)
This quantitative study examined 100 Pakistani ESL learners’ beliefs about both learning English language learning and their learning strategy use. It focused on the relationship between language learning strategies used by the Pakistani ESL learners to learn the English language and the beliefs they held about it. To collect the data on learners’ beliefs about language learning and their learning strategy use, two instruments, i) beliefs about language learning inventory (BALLI) (Horwitz,1987) and ii) strategy inventory for language learning (SILL) (Oxford,1990, were used. Learners’ responses were computed through descriptive statistics. Factor analysis was run to determine the primary factors for the beliefs and the strategy inventory and the Pearson correlation analysis was carried to compute the relationship between two variables namely belief factors and the strategic factors. The results of the study revealed that these learners held overall positive and realistic beliefs for English language learning, and compensation strategies were found to be the most frequently used strategies, followed by memory, social, affective, cognitive and meta-cognitive strategies respectively. Further, the results of the study showed that the Pakistani ESL learners’ beliefs for formal oral practices were positively correlated with all strategic factors except compensation strategies. The participants’ beliefs about self-efficacy and confidence were positively correlated with memory as well as social and affective strategies but negatively correlated with compensation strategies. The participants’ beliefs about the perceived difficulty of learning English were not found positively correlated with any language learning strategy factor. The assumption that learners’ beliefs are linked to their use of learning strategies was affirmed. This study will enhance the understanding of teachers, language learners, and curriculum designers about language learning beliefs and language learning strategy use in Pakistan.